Vision-related quality of life among patients with keratoconus: a cross sectional study - Al Zabadi, Hamzeh; Shehadeh, Mohammad; Amro, Lubna; Ghattass, Nadeen; Taha, Ibrahim (Frontiers in Medicine, 2023)
Purpose The present study aimed to evaluate the quality of life of keratoconus patients residing in Nablus city, Palestine. Furthermore, we investigated the possible correlation between Pentacam topographic indices and the quality of life of patients with keratoconus. Methods This cross-sectional study evaluated keratoconus patients at An-Najah University Hospital in 2019, diagnosed through clinical examination and corneal tomography. A control group was randomly selected from non-keratoconus patients with normal tomography. The NEI-VFQ-25 questionnaire was administered during face-to-face interviews to compare both groups. NEI-VFQ-25 assesses vision-related quality of life and is a validated tool. Results Keratoconus patients' quality of life is significantly impacted, mainly in near and distant vision, general vision, mental health, and social health, but not in general health, ocular pain, color vision, role difficulties, or dependency. Visual acuity is significantly affected in both eyes of keratoconus patients. Conclusions Patients with keratoconus exhibit a decreased quality of life related to vision, with physical, emotional, and social impairments demonstrated by the NEI-VFQ-25 when compared to controls. Since keratoconus patients are typically young adults in their productive years, understanding their concerns about their future is an important public health aspect that can aid in modifying their treatments. By addressing the specific needs of this patient population, healthcare providers can better support their long-term well-being and quality of life.